2021
DOI: 10.5603/mrj.2021.0029
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest and COVID-19 pandemic

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The COVID-19 pandemic significantly changed the functioning of health care systems worldwide. The emergency systems, as the first line of management of infectious patients, were particularly affected by the pandemic and required modernization of the daily routine [3,4]. Previous studies showed that Emergency Medical Service (EMS) personnel was exposed to a high level of stress, anxiety, and fear caused by new and difficult working conditions that affected also their family lives [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic significantly changed the functioning of health care systems worldwide. The emergency systems, as the first line of management of infectious patients, were particularly affected by the pandemic and required modernization of the daily routine [3,4]. Previous studies showed that Emergency Medical Service (EMS) personnel was exposed to a high level of stress, anxiety, and fear caused by new and difficult working conditions that affected also their family lives [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable prolongation of the EMS response time was found in 2020 in comparison with the two-year pre-pandemic period, with the longest delay in the autumn, which corresponded to the peak of the second wave of COVID-19 infections in Poland [1]. These interesting observations complement the image of EMS functioning during the pandemic time [3][4][5][6][7]. Reduction in the rate of hospitalizations for acute heart failure was even more pronounced at the beginning of the pandemic in Poland during the first public lockdown from March to May 2020 [8].…”
mentioning
confidence: 53%
“…In late 2019 a highly pathogenic novel coronavirus of severe acute respiratory syndrome (SARS-CoV-2) emerged, causing a global pandemic of coronavirus disease-2019 . This new hitherto unknown disease, has had a huge devastating impact on the lives of individuals and entire societies [1][2][3][4][5][6][7][8][9][10][11][12]. There are three stages of the COVID-19:…”
Section: Introductionmentioning
confidence: 99%